Family Support and The Role of Health Professionals on Parent’s Perspectives of Covid-19 Vaccination in Child - Ayu Nurdiyan; Evi Susanti (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2023)
Background: The administration of Covid-19 immunization is one of the measures taken to prevent Covid-19 infectious diseases among vulnerable groups, such as children aged 6 to 11 years. However, the majority of parents continue to have a poor opinion of the safety of the Covid-19 vaccine and its side effects, since just 5.7% of parents of 564,833 children in West Sumatra allow their children to get vaccinated. Purpose: This study aimed to investigate the determinants of parents’ perception towards vaccinating their children against COVID-19. Methods: This study employed a quantitative methodology and a Cross Sectional design. This research was conducted at an elementary school in Bukittinggi. The study population consisted of 466 children. In this study, 100 respondents were consecutively selected as samples. The tool employed was a valid and reliable questionnaire, and the data were analyzed using a chi-square test with a significance level of 0.05. Results: the results of the statistical test of bivariate analysis stated that there was a relationship between family support and perspective, p Value 0.05 (< 0.05), and there was no relationship between the role of health workers and perspective p Value 0.318 (> 0.05). Conclusion: it is important to increase the positive perspective of parents regarding vaccination, this can be done through health promotion by using various media so that not only parents get but also increase the perception of family support.